The effectiveness of non-standard monetary policy measures: evidence from survey data - Carlo Altavilla; Domenico Giannone (European Central Bank (ECB), 2016)
We assess professional forecasters' perceptions of the effects of the unconventional monetary policy measures announced by the US Federal Reserve after the collapse of Lehman Brothers. Using survey data, collected at individual level, we analyze the change in the forecasts for Treasury and corporate bond yields around the announcement dates of the non-standard measures. We find that forecasters expected bond yields to drop significantly for at least one year after the announcement of accommodative policies.
Keywords: E58; E65; 330; forward guidance; large scale asset purchases; operation twist; quantitative easing; survey of professional forecasters; tapering